Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques

Le langage n'est pas neutre. Petit guide de rédaction féministe - Institut de recherches et d'études féministes (FéminÉtudes, 2014)
« Le but de cette publication est d’offrir un guide succinct visant à initier aux modes de féminisation. Il vise surtout à encourager les pratiques de féminisation au quotidien, autant dans les activités courantes que dans la vie académique. Il vise également à étendre les pratiques de féminisation au-delà des milieux militants et féministes, en proposant une pluralité de modes de féminisation qui puissent convenir aux plus de contextes possible. Finalement, il propose aux personnes intéressées des guides et des ressources pertinentes pour approfondir le sujet. » (2014, 1) ***
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; féminétudes; genre; identités LGBTQIA2+; militance; outils; ouvrages de références; pédagogie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; thématiques; écriture inclusive